Driyarkara's Educational Thought and Its Relevance to Peace Education - Nababan, Hokkop Fritles; Abrar, Abrar; Martha, Nur Aeni (Journal La Sociale, 2024)
Indonesian society is prone to various conflicts, both political and social. These conflicts not only cause material losses but also claim lives. Therefore, a step is needed to prepare society to face conflicts non-violently, namely through peace education. This paper examines Driyarkara's thoughts on education, which have relevance to peace education. This research uses a library research method and is analyzed using a content analysis method. The primary purpose of education for Driyarkara is to form young people into perfect human beings who not only have good intellect but also good character and morals and are able to live peacefully and harmoniously with other humans. To achieve a peaceful and harmonious personality, education must teach young people to be culturally literate, meaning to know their own culture and understand the cultures of others. Another step that must be taken is to include peace values in every learning process, including every subject, such as social, exact, and language subjects. For Driyarkara, equipping young people with knowledge of culture and peace will create a tolerant younger generation who are positive and able to find solutions to any conflicts that arise.